PROFIL PERTANYAAN SISWA TUNANETRA KELAS IX SMPLB YKAB SURAKARTA DALAM PEMBELAJARAN MATEMATIKA - Khoiriyah, Siti (JURNAL E-DUMATH, 2015)
AbstractÂ Thinking can be drilled to the student by developing question skill during teaching process. Personal life quality is determined from question quality; the more qualified a question the more success a person in life. Therefore, this study analyzed the students question to find out the students question quality. The subject of this study is IX class of SMPLB YKAB students Surakarta. The data was found by observation with handy cam. The data analysis was conducted through data reduction, data presentation and conclusion. From the data analysis was found the result that 89 questions from the students consist of 46 (51, 68 %) questions that consist of C1, 2 elements (2,25 %) questions that consist of C2, 25 elements (28,09 %) questions that consist of C4 elements. Based on the finding of the study could be conclude that majority of visual impaired students in low categorize because of having C1, C2, and C3 elements.Keywords : visual impaired students question, mathematics learning.